2021
DOI: 10.1080/09638288.2021.1963853
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, physical functioning, and psychosocial function among patients with achondroplasia:a targeted literature review

Abstract: Purpose: Achondroplasia (ACH) is the most common form of skeletal dysplasia, resulting in disproportionate short stature and medical complications. We review the literature on physical functioning, psychosocial function, and quality of life (QoL) in ACH individuals compared to average stature individuals or other short stature conditions. Studies that assess the association between these outcomes and height, limb length/lengthening surgery in ACH patients are also summarized. Materials and methods: PubMed/MEDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…It has been well established that individuals with achondroplasia have a reduced HRQoL compared with the healthy population [ 3 , 19 21 ]. Several factors may contribute to this, depending on the age of the patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been well established that individuals with achondroplasia have a reduced HRQoL compared with the healthy population [ 3 , 19 21 ]. Several factors may contribute to this, depending on the age of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that short stature and skeletal dysplasia negatively impact on the ability of individuals to perform activities of daily living and on independence of adults [ 3 , 22 ]. Literature suggests that in individuals with achondroplasia, limitations in physical functioning and reduced HRQoL are at least partly due to disproportionate short stature [ 3 ]. In our study, 73% of the panelists agreed that a final height < 140 cm likely has an independent negative impact on physical HRQoL (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S hort stature has an extraordinary impact on achondroplastic patients' daily life activities, causing physical limitations, problems with social integration and body image, and decreased self-esteem. 1 As a result, limb lengthening is increasingly being used to treat achondroplastic patients. These surgical techniques have undergone significant development in recent years.…”
mentioning
confidence: 99%